A Land Far Away - Guenther Grohall; Yuri Yegorov (FIW - Research Centre International Economics, 2011)
What goods to export and where to sell them? Our research was pursuing these two major goals. The first one is related to detecting countries where Austria has good perspectives for boosting its export. The basic idea was to use macroeconomic data set detecting the significant variables. We found that besides the GDP of importer and distance, there are more important variables like being landlocked, language, inflation, and so forth. We found recent GDP growth rate to be non-significant in more than just the very basic models. Taking all explanatory variables into account we could calculate the country-effects, telling us how Austrian exporters are under or over-represented within each country. It is argued that exporters could put additional efforts into quickly growing countries where Austria is still under-represented. The second goal was a more detailed view on the role of transport costs. Gravity model was shown to be correct and robust (even for a class of functions of distance). The detailed accounting for transport costs requires consideration of different transport modes and ratios of value to weight. Distance suppresses trade of cheap goods most, suggesting that Austria has no disadvantage in export of high-tech goods (like pharmaceutics and complex machines) over long distances. In particular, pharmaceutical sector has growing potential and trade with Russia is one of its perspectives.
Keywords: F14; L90; R40; 330; International Trade; Gravity Model; Transport Cost; Growth; Advantage